What it Means to be “Handmade”? - Teah, Min; Hatton-Jones, Siobhan; Loi, Clara (2019)
In the day and age where brands are seeking to distinct their products and production, one of the methods which are employed is to create handmade products. However, there is little consensus as to what it means in the eyes of consumers. Therefore, the aim of this study is the conceptualise the meaning of handmade. Data is collected from 850 respondents using open-ended questions. A thematic analysis is conducted to generate the themes and consumer perceptions towards handmade. The findings provide implications for brand managers, practitioners and researchers on how to utilize the “handmade” cue.